Minnesota Multiphasic Personality Inventory 2 (MMPI 2) examination in patients with benzodiazepine addiction in Yogyakarta - Silas Henry Ismanto; Irwan Supriyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
Addiction is a major health problem in Indonesia. The prevalence and pattern of drugsaddiction shifted according to changes in personality, stressors, or increasing responsibilityas people grow. Individual personality will affect their tendency to develop drug addiction.Benzodiazepines abuse has steadily increased. Unlike other type drugs of abuse, thecharacteristics of benzodiazepine abusers are greatly varied. Therefore, the personalitytraits and social economic factors involved in the benzodiazepine addiction are unique.In this study we evaluated the personality traits of patient with benzodiazepine addictionin Yogyakarta using Minnesota Multiphasic Personality Inventory (MMPI) 2 test. Thisstudy was a descriptive analytic study with a cross sectional design. Subjects were 39benzodiazepine addicts obtained from private psychiatrist practices in Yogyakarta. Theinstruments used were questionnaire for personal information and MMPI 2. Statisticalanalysis was conducted with SPSS ver. 17 and significance level was defined at p<0.05.MMPI 2 test revealed a low total mental capacity index and a low basic personality index(OCEAN: openness, conscientiousness, extraversion, agreeableness, and neuroticism).The clinical profiles examination showed profile of somatic symptoms due to psychologicaldisturbances, clinical symptoms of overt suspiciousness, overt negative emotionality,clinical symptoms of depression, symptoms of psychopathic behaviours (antisocial),emotional difficulty in interpersonal relationship, clinical symptoms related to overtemotion, and weird and bizarre psychological experiences. There are certain personalityvariables that may be important predictors for benzodiazepine addiction identified in thisstudy.